(untitled) (Global Journal of Human-Social Science, 2022)
This paper examined the Sufi culture of Maizbhandar Sufism is the spiritual and mystical branch of Islam with a concrete system of belief customs and practices It also focuses on the belief traditions and practices of Maizbhandari Sufi culture Maizbhandar has millions of followers who are following this Sufi culture An ethnographic approach has been applied to conduct the study The center of Maizbhandar Fatikcchari Chittagong was the site field of the study There were 30 in-depth interview respondents 18 focus group discussion respondents and 1 key informant of the study and all of them were selected through a purposive sampling Qualitative data were collected from the respondents and a thematic analysis method was used for data analysis